Подавление синхронной помехи в ЯКР с модуляцией Зеемана - Politanskii, L. F.; Samila, A. P.; Khandozhko, V. А. (PE "Politekhperiodika", Book and Journal Publishers, 2012)
The principles of frequency and Zeeman modulation in nuclear quadrupole resonance were considered, and the advantages of the latter were shown. The authors propose a method to eliminate the synchronous noise caused by switching of the magnetic field. Results of observations of the resonance line with 14N in the hexamethylenetetramine sample weighing 2 g were given.